CD137 costimulation is associated with reduced herpetic stromal keratitis and with developing normal CD8+ T cells in trigeminal ganglia. (29th June 2022) - Yin, Xiao-Tang; Baugnon, Nicholas K.; Krishnan, Rohini; Potter, Chloe A.; Yarlagadda, Sudha; Keadle, Tammie L.; Stuart, Patrick M.
Abstract : Costimulatory interactions can be critical in developing immune responses to infectious agents. We recently reported that herpes simplex type 1 (HSV-1) infections of the cornea require a functional CD28-CD80/86 interaction to not only reduce the likelihood of encephalitis, but also to mediate herpetic stromal keratitis (HSK) following viral reactivation. In this same spirit we decided to determine the role that CD137 costimulation plays during HSK. Using both B6-CD137L -/- mice, as well as antagonistic and agonistic antibodies to CD137 we characterize the immune response and to what extent CD137 plays an important role during this disease. Immune responses were measured in both the cornea and in the trigeminal ganglia where the virus forms a latent infection. We demonstrate that CD137 costimulation leads to reduced corneal disease. Interestingly, we observed that lack of CD137 costimulation resulted in significantly reduced CD8 + T expansion and function in the trigeminal ganglia. Finally, we showed that viruses that have been genetically altered to express CD137 display significantly reduced corneal disease, though they did present similar levels of trigeminal infection and peripheral virus production following reactivation of a latent infection. CD137 interactions lead to reduced HSK and are necessary to develop robust trigeminal CD8 + T cell responses.